Moisture Variability in the East Pearl River Basin since 1894 CE Inferred from Tree Ring Records - Teng Li; Jinbao Li; Tsun Fung Au; David D. Zhang (Atmosphere, 2020)
Short-term climate change in South China has been extensively studied based on meteorological or hydrological records. However, tree ring-based long-term climate change research is rare, especially in the Pearl River basin, owing to the difficulty in finding old-aged trees. Here, we present a 200-year tree ring width chronology of Pinus kwangtungensis in the east Pearl River basin with reliable coverage from 1894 to 2014. Based on the significant climate-growth relationship between tree growth and annual self-calibrating Palmer drought severity index (scPDSI) from previous May to current April, the pMay-cApr scPDSI was reconstructed for the period 1894–2014. The reconstruction reveals four dry periods during 1899–1924, 1962–1974, 1988–1994, and 2003–2014, and four wet periods during 1894–1898, 1925–1961, 1975–1987, and 1995–2002. Significant spatial correlations between the reconstructed scPDSI and the Climatic Research Unit (CRU) gridded scPDSI indicate that our reconstruction can effectively represent regional moisture variability in the Pearl River basin. Spatial correlations with global sea surface temperatures (SSTs) show that our reconstruction is negatively correlated with northern and western Pacific SSTs while positively correlated with eastern Pacific SSTs, suggesting that SST variability in these domains strongly affects moisture change in the Pearl River basin.